Representation of Social Inequality in the Film Jakarta Vs Everybody - Fitrianto, Alfian Bagus; Sumarlan, Iman (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
Urbanization in major cities such as Jakarta frequently results in heightened social inequality and economic segregation, further widening the gap between different societal groups. Jakarta vs Everybody portrays these urban challenges by depicting the harsh realities of city life through characters ensnared in crime and economic hardship. This study adopts a qualitative methodology, employing semiotic and discourse analysis to examine how the film represents social inequality in the context of urbanization. The findings reveal that the film effectively illustrates marginalization, social injustice, and economic segregation present in Jakarta. Specifically, it highlights disparities in access to opportunities and resources among various social groups, which drive the main characters toward a life of crime as a shortcut to survival. These results bolster existing theories of social and economic segregation in urbanized settings, demonstrating that inequality in large cities extends beyond economic factors and shapes broader social and cultural dynamics. The implications of this research underscore the need to address uneven urbanization, which exacerbates inequality and crime in big cities. The film serves not only as a medium for raising social awareness but also as a platform for provoking deeper discussions on spatial policies and social justice in urban environments. Consequently, this study contributes to the literature on the interaction between popular media and social issue representation in urban society.